PENGARUH DOSIS PUPUK KANDANG TERHADAP STABILITAS AGREGAT TANAH PADA SISTEM PERTANIAN ORGANIK - - Mustoyo; Bistok Hasiholan Simanjuntak; - Suprihati (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
Organic matter is important to soil aggregate stability. The research of effect dosage of goat manure tos oil aggregate in organic farming system was do neon Andisols soil in Permata Hati Farm, CiburialHamlet, North Tugu village, Cisarua sub-district, Bogor district, West Java province. The research was conducted on October 2012 until the end of February 2013. The research purposes are: a) Know the goat manure’s dosage influence on soil aggregate in organik farming system, b) Determine the dos age of goat manure that can provide the best Mean Weight Diameter (MWD) and Aggregate Stability Index (ASI)in organik farming system. The research used randomized completely block design (RCBD) with 6 treatments and 3 replications. Goat manure dosage were used as treatments are 0 ton ha-1, 5 ton ha-1, 10 ton ha-1, 15 ton ha-1, 20 ton ha-1, and 25 ton ha-1. Data was analyzed by ANOVA and Duncan’sMultiple Range Test (DMRT) at 5% level. The research results are showed, with initial number of C-organic >4.5%, goat manure application was significant to change soil aggregate. Goat Manure 5 ton ha-1was enough to increasing Mean Weight Diameter (MWD) and ASI (Aggregate Stability Index).